John Thacker: The Art of Cookery (1758) - Jaine, Tom (Petits Propos Culinaires, 2005)
John Thacker: The Art of Cookery (1758), facsimile edition, with an introduction by Ivan Day: Southover Press, 2005: ISBN 1870962206: 400pp., harback, £25.